Evaluation of the Implementation of Mobuya Learning Media in Elementary Schools - Pranata, Alvira; Syamsijulianto, Tri (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The implementation of learning media is a crucial aspect in enhancing the effectiveness of the education process in elementary schools, and one increasingly recognized learning medium is Mobuya Learning Media. This article aims to evaluate the implementation of Mobuya Learning Media in Elementary Schools and assess its impact on the quality of learning. The data collection method for the article involves using reference management tools for publications and searching the Google Scholar database using Publish or Perish (PoP 8). The article search process was conducted with keywords such as "Learning Media, Evaluation, and Mobuya Learning Media" in the title and abstract. This evaluation is expected to provide a deep understanding of Mobuya's potential as a learning medium at the elementary school level. The research involves qualitative and quantitative data analysis to provide a comprehensive overview of the impact of implementing Mobuya Learning Media on the learning process in elementary schools. The findings from this research are anticipated to contribute to the development of more innovative learning strategies at the elementary level